Adsorption Isotherm of Carbon Microparticles Prepared from Pumpkin (Cucurbita maxima) Seeds for Dye Removal - Nandiyanto, Asep Bayu Dani; Hofifah, Siti Nur; Inayah, Hilma Tahsilul; Putri, Silmi Ridwan; Apriliani, Siti Saffanah; Anggraeni, Sri; Usdiyana, Dian; Usdiyana, Dian; Rahmat, Ali (Iraqi Journal of Science, 2021)
This study aims to evaluate the adsorption isotherm of carbon microparticles prepared from pumpkin (Cucurbita maxima) seeds for adsorbing curcumin (as a model of dye). The results were derived and compared using the kinetics approach based on several standard adsorption isotherm models, namely the Langmuir, Temkin, Freundlich, and Dubinin-Radushkevich models. The second aim is to evaluate the effects of carbon particle size (from 100 to 1000 mm) on the adsorption characteristics. The experimental results showed that the adsorption on the surface of carbon microparticles occurred in monolayer with a physical phenomenon. This is because the active areas are located only on the outer surface of carbon and no surface structure in the carbon is available. This is confirmed by the fact that the produced carbon has less porosity and the pores themselves are mostly produced from the release of inorganic contents during carbon synthesis, while the amount of inorganic content is very less. The confirmation of the adsorption profile was also achieved by testing various sizes of carbon microparticles. Smaller particles have direct impacts on the improvement of adsorption capacity, which is due to the existence of a larger surface area, a larger number of adsorption sites, and additional cooperative adsorption, i.e. adsorbate-adsorbate interaction. Understanding the adsorption phenomena occurring on carbon particles is useful for further developments and applications, such as those of catalysts and adsorbents, especially concerning the production of carbon materials from organic waste.